1996
DOI: 10.1097/00000658-199601000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment of Severely Burned Patients

Abstract: ObjectiveThe authors provide an update on a multidisciplinary approach to the treatment of severely burned patients. A review of studies and clinical trials from the past to the present include fluid resuscitation, sepsis, immune function, hypermetabolism, early excision, wound healing, scar formation, and inhalation injury. Summary Background DataAdvances in treating initial burn shock, infection control, early wound closure, and modulation of the hypermetabolic response have decreased morbidity and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(85 citation statements)
references
References 83 publications
1
78
0
3
Order By: Relevance
“…The effect of MEBO, however, cannot be equated to that of other topical agents. It has a different mechanism of action regarding eschar separation, moreover, it is peculiar in providing the necessary moist environment in conformity with the long-held and recently confirmed belief that wounds, including burn wounds, heal best in a moist environment [5]. Whether treatment of second degree burns with MEBO application alone may reduce the need for early surgical excision and skin grafting without compromising the final outcome still needs to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of MEBO, however, cannot be equated to that of other topical agents. It has a different mechanism of action regarding eschar separation, moreover, it is peculiar in providing the necessary moist environment in conformity with the long-held and recently confirmed belief that wounds, including burn wounds, heal best in a moist environment [5]. Whether treatment of second degree burns with MEBO application alone may reduce the need for early surgical excision and skin grafting without compromising the final outcome still needs to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional burn wound management involved applying topical antibiotics in dressings until the eschar separated. Separation occurred by liquefaction of necrotic burn tissue by proteolytic enzymes released from proliferating pathogens within the wound [5]. More than two decades ago, Janzekovic demonstrated that early removal of the burn tissue by tangential excision reduced pain, number of operative procedures and length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation injury should be suspected if the patient was burned in an enclosed space, has facial burns, and/or develops progressive hoarseness or stridor or a cough productive of carbonaceous sputum. The clinical effects of thermal inhalation injury typically become manifest within a few hours after injury, whereas chemical injury of the lower respiratory tract progresses more slowly (e.g., 1 to 2 days) (101,322). Stridor that develops immediately after heat injury associated with an increased respiratory rate, worsening hypoxemia, and trouble expectorating secretions are signs of worsening edema of the upper airway (e.g., glottis), and immediate airway intubation is required to maintain patency (15,95,275).…”
Section: Inhalation Injurymentioning
confidence: 99%
“…Most patients with inhalation injury have a normal chest radiograph at presentation and presence of pulmonary opacities on initial chest films has been implicated as a marker of severe injury and a poor prognosis. 10,13,14 Computed tomography of the chest may be helpful as an early predictor of smoke inhalation severity based on airway wall thickness. 15,16 Chest computed tomography (CT) scans may show groundglass opacities in a peribronchial distribution and/or patchy peribronchial consolidations.…”
Section: Discussionmentioning
confidence: 99%